The Spatiotemporal Characteristics and Rationality of Emerging Megacity Urban Expansion: A Case Study of Zhengzhou in Central China - Cai, Enxiang; Bi, Qingsheng; Lu, Jie; Hou, Heping (Frontiers in Environmental Science, 2022)
Studies on urban expansion in megacities is essential for managing urban sprawl and thus promoting high-quality development. This paper selected the emerging megacity Zhengzhou as the research area, uses the spatial analysis method to quantify the spatiotemporal characteristics of urban expansion from 1990 to 2020, and evaluates the rationality of urban expansion on the basis of the elasticity index and a comparison with other megacities. Results demonstrated that (1) Zhengzhou experienced great urban expansion from 1990 to 2020 and showed a trend of "steady-fast-slow", with steady expansion from 1990 to 2000, fast expansion from 2000 to 2010, and slow expansion after 2010; (2) Zhengzhou’s urban expansion has obvious imbalance and spatial disorder, being mainly concentrated in the urban central area and characterized by sprawl or a leap in space; (3) The occupation of cultivated land by urban expansion in Zhengzhou has gradually decreased, but the occupation of ecological land such as water areas has increased significantly, which may lead to a series of negative ecological effects. (4) Zhengzhou’s urban expansion was inefficient, while the utilization intensity and economic benefits of Zhengzhou’s urban construction land have improved, but was relatively lower than those of other megacities in China. The findings have important reference significance for promoting sustainable urban expansion of megacities and achieving regional sustainable development.